Outcome of tibial fractures in children managed by titanium elastic nailing system (TENS) - Shrestha, Aayush; Gupta, Hemant K. (Grande Medical Journal, 2021)
Introduction: Fractures of the tibia are among the most common fractures of the long bone in children and adolescents. Although the most common method of management of tibial shaft is through closed reduction and cast application, operative management may be required in cases such as unstable tibia fractures in which adequate reduction cannot be achieved, loss of reduction of the fracture, fractures associated with other injuries and open fractures. Titanium elastic nailing system (TENS) can be a good option for fractures that are displaced, unstable and difficult to manage in plaster cast. TENS is a simple, minimally invasive, stable and effective method with excellent outcome and minimal complications. Methods: This was a prospective study in which children between the ages of 6 to 14 years with diaphyseal fracture tibia treated with intramedullary fixation with TENS. All the patients were followed up for period of at least 6 months. The alignment of fracture, range of motion of knee joint and complications were evaluated during follow-up examinations. The time taken for the union of the fracture was evaluated with the help of the RUST criteria and final outcome was measured by Flynn’s criteria1. Results: A total of 33 patients (22 were males) with the mean age of 9.51 years were studied. The mean duration of surgery was about 44 minutes. Oblique pattern of fracture was the most common type while middle third of the diaphysis was most commonly involved. The average duration of hospital stay was 7.8 days with average time of union being 11.39 weeks (range: 6-22 weeks). The most common complication seen in 2 patients was skin irritation due to prominence of the implant. None of the fracture had angulation greater than 10 degrees in coronal or sagittal planes and 1 cm of leg length discrepancy (shortening) was seen in a case of comminuted fracture. The outcome according to Flynn’s criteria was excellent in 28 cases, good in 4 cases and fair in 1 case. Conclusions: TENS is an effective method that for the treatment of tibial shaft fractures in children in preventing damage to the epiphysis without interfering with fracture hematoma, while avoiding stiffness of the knee and limb length discrepancies and thereby decreasing the morbidity of the patient. The operative procedure is simple, has a low rate of complication, and prevents damage to the growing physis. It allows for early mobilization and decreases the duration of hospital stay.